ON THE ISSUE OF SIMILARITIES AND DIFFERENCES BETWEEN THE LEGAL POSITION AND THE DECISION OF THE RUSSIAN CONSTITUTIONAL COURT - M. A. Mokoseyeva (Russian Journal of Economics and Law)
Objective: to determine the differences between the legal position and the decision of the constitutional justice authority, to identify the essence of the legal positions of the constitutional control bodies as a complex legal phenomenon and its impact on the legal system of the Russian Federation. Methods: scientific analysis (analysis of theoretical sources); synthesis method; systemic-structural; generalization of materials on the theme studied, structural-functional, historical; specific scientific methods: techno-legal, comparative legal, formal legal. Results: the article defines the concept of the legal position of the Russian constitutional court, the characteristics and essence of the phenomenon; we study the formation of the legal positions of the Russian constitutional court. Scientific novelty: to date in the legal literature there is no consensus on the concept and juridical nature of the legal positions of the Russian constitutional court, their correlation with the decision of the specified authority. The author reveals the essence of the legal positions of the constitutional controlbodies as a complex legal phenomenon and its impact on the Russian legal system, highlights the similarities and differences between the legal position and the decision of the constitutional justice. Practical significance: the theoretical and practical proposals of the author may be used in the improvement of the Russian legislation, as well as in lectures and workshops on the subjects related to the research topic.